اصدقاء الثورة الجزائرية و دورهم في دعم القضية الجزائرية و دورهم في دعم القضية الجزائ الجزائرية - محمد يطو اسلام; د/ محمد محمدي (جامعة عمار ثليجي بالاغواط, 2025)
ملخص الدراسة بالعربية: وفي ختام هذه الدراسة، يتضح أن التجربة الاستعمارية الفرنسية في الجزائر كشفت عن انقسام واضح داخل النخبة الفرنسية بين مؤيد للاستعمار ومعارض له، ما يعكس تنوّع المواقف واختلاف الانتماءات، وقد لعب المثقفون اليساريون دورًا بارزًا في فضح ممارسات القمع، رغم تردد بعضهم في المطالبة الصريحة باستقلال الجزائر، وبرزت شخصيات كفرنسيس جونسون و فرانز فانون وهنري علاق ممن تجاوزوا النقد النظري نحو دعم عملي وفعّال للثورة الجزائرية. وقد ساهمت مواقفهم وكتاباتهم في كشف جرائم الاحتلال أمام العالم ومنح القضية الجزائرية زخمًا أخلاقيًا دوليًا. وتظل تجربة هنري علاق خصوصًا، مثالًا نادرًا في الدفاع عن القيم الإنسانية ومقاومة الظلم بشجاعة. ملخص الدراسة بالانجلزية: In conclusion, this study reveals that the French colonial experience in Algeria exposed a clear divide within the French elite between supporters and opponents of colonialism, reflecting the diversity of perspectives and differing ideological affiliations. Leftist intellectuals played a significant role in denouncing acts of repression, despite some of them hesitating to openly demand Algerian independence. Prominent figures such as Francis Jeanson, Frantz Fanon, and Henri Alleg stood out by moving beyond theoretical critique to offer practical and effective support for the Algerian revolution. Their positions and writings contributed to exposing the crimes of colonialism to the world and gave the Algerian cause international moral momentum. Henri Alleg’s experience, in particular, remains a rare example of defending human values and resisting injustice with courage.
هنري علاق انموذجا